T&T Clark handbook of public theology - Hübenthal, Christoph 1961-; Alpers, Christiane 1987- (T&T Clark, 2022)
"T&T Clark Handbook of Public Theology introduces the various philosophical and theological positions and approaches in the emerging discourse of public theology. Distinguishing public theology from political theology, as well as from liberation theology, this book clarifies central terms like 'public sphere', 'the secular', and 'post-secularity' in order to highlight the specific characteristics of public theology. Its particular focus lies on the ways in which much of public theology has established itself as a contextual theology in politically secular societies, aiming to continue the apologetical tradition in this specific context. Depending on what is regarded as the most pressing challenge for the reasonable defence of the Christian hope in liberal democracies, public theologians have focused on (social) ethics, ecclesiology, or Soteriology, with the aim to strengthen the virtues needed for democratic citizenship. Here, attention is being paid to Protestant, Catholic and Orthodox perspectives. The volume further illustrates the characteristics of the discourse by introducing the ways in which public theologians have responded to concrete challenges arising in the spheres of politics, economics, ecology, sports, culture, and religion. To highlight the international scope of the public theological discourse, the volume concludes with a summarizing overview of public theological debates in Africa, Asia, Australia, Europe, North America and South America"
Keywords: Öffentliche Theologie; Public theology; Aufsatzsammlung